Diagnostic Accuracy of Lachman Test in diagnosing Anterior Cruciate Ligament injury in relation to Magnetic Resonance Imaging (MRI) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the accuracy of Lachman test in diagnosing tears of Anterior Cruciate Ligament (ACL) taking Magnetic Resonance Imaging (MRI) as gold standard.Methodology: Our study was cross sectional in design and all patients with knee pain and instability after trauma were enrolled. Lachman test was performed followed by MRI of the same knee. Sensitivity of Lachman test, its specificity, positive predictive value and negative predictive value were determined while taking Magnetic Resonance Imaging(MRI) as the gold standard for comparison.Results: There were 110 (86.61%) males and 17 (13.38%) females. True positive patients of ACL tear based upon Lachman test were 36(28.34%) while true negative were 87 (68.50%). False positive patients of ACL tears were 1 (0.78%) and false negative 3 (2.36%). The Lachman test was found to be 92.30% sensitive and 98.86% specific for detecting ACL tears. The positive predictive value of Lachman test was 97.29% and negative predictive value 96.66%. We found that Lachman test had a diagnostic accuracy of 96.85%.Conclusion: Lachman test was found to be more specific and had high negative predictive value in detecting ACL tear. It can be used as a diagnostic tool for determining tears of  anterior cruciate ligament in place of MRI in uncomplicated cases.